Vetenskapen i verkligheten - Williams, Anna (Tidskrift för litteraturvetenskap, 2012)
The Borders of Academic Writing This article contributes to the ongoing discussion of language and communication within literary scholarship. While public debate has been concerned with the so-called ‘crisis of the Humanities’, research and scholarly achievements continue to be produced, despite alarming reports about the uncertain future of the field. Throughout modern humanistic studies, scholars have communicated with colleagues as well as with the public, contributing vital knowledge about human thought and society. The article stresses the need to discuss the definition and methodology of humanistic research. It also stresses the importance of a wide variety of publications and publishing sites to maintain the depth and width of literary studies.